Natural Variability in Caribbean Coral Physiology and Implications for Coral Bleaching Resilience - Chapron, Leila; Schoepf, Verena; Levas, Stephen J.; Aschaffenburg, Matthew D.; Warner, Mark E.; Grottoli, Andréa G. (Frontiers in Marine Science, 2022)
Coral reefs are among the most diverse and complex ecosystems in the world that provide important ecological and economical services. Increases in sea surface temperature linked to global climate change threatens these ecosystems by inducing coral bleaching. However, it is not fully known if natural intra- or inter-annual physiological variability is linked to bleaching resilience or recovery capacity of corals. Here, we monitored the coral physiology of three common Caribbean species (Porites divaricata, Porites astreoides, Orbicella faveolata) at six time points over 2 years by measuring the following traits: calcification, biomass, lipids, proteins, carbohydrates, chlorophyll a, algal endosymbiont density, stable carbon isotopes of the host and endosymbiotic algae, and the stable carbon and oxygen isotopes of the skeleton. The overall physiological profile of all three species varied over time and that of P. divaricata was consistently different from the two other coral species. Porites divaricata had higher energy reserves coupled with higher contributions of heterotrophically derived carbon to host tissues than both P. astreoides and O. faveolata. Consistently higher overall energy reserves and heterotrophic contributions to tissues appear to buffer against environmental stress, including bleaching events. Thus, natural physiological variability among coral species appears to be a stronger predictor of coral bleaching resilience than intra- or inter-annual physiological variability within a coral species.